A new method for numerical solution of checkerboard fields - Stein A. Berggren; Dag Lukkassen; Annette Meidell; Leon Simula (Journal of Applied Mathematics)
We consider a generalized version of the standard checkerboard and discuss the difficulties of finding the corresponding field by standard numerical treatment. A new numerical method is presented which converges independently of the local conductivities.